Has the Income Share of the Middle and Upper-Middle Been Stable Around the 50/50 Rule , or Has It Converged Towards That Level? the Palma Ratio Revisited - Palma-Penco, J (WILEY-BLACKWELL, 2014)
In an article published in this journal in 2011, an alternative measure of inequality was suggested, which has subsequently become known as the Palma Ratio . In this new article, the author of the original proposal revisits the argument for such a measure. Using new data, he examines whether the current remarkable homogeneity in the income share of the middle and upper-middle around the world the foundation of the so-called Palma Ratio is an historically stable stylized fact, or whether it is a new phenomenon, the outcome of a process of convergence towards the current 50/50 Rule (in which half of the population in each country located within deciles 5 to 9 tends to appropriate about 50 per cent of the national income, or just above). Although partly written in response to a comment on the 2011 paper (published in this issue), the article also makes a substantive further contribution to the literature on inequality and the statistics to measure it.